Faktor-Faktor yang Mempengaruhi Pendapatan Usahatani Padi Lebak di Desa Pemulutan Ulu Kabupaten Ogan Ilir - Chuzaimah Chuzaimah; Noprianto Noprianto; E. Lastinawati; A. Febriyansyah (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Chuzaimah et al, 2016.Â The Factors that affect to Swamp Rice Farming IncomeÂ in Pemulutan Ulu Village, Ogan Ilir District. JLSO 5(1):27-34.Good management of rice farming is indispensable in order to increase farmers' income. Good management can not be separated from social and economic characteristics inherent in farmers. This research aimed to determine the factors that affecting swamp rice farming income. The research used survey method, where Pemulutan Ulu Village, Pemulutan Subdistrict, Ogan Ilir District been intentionally (purposive) as a research location. The sample was selected as many as 30 farmers from 302 population using stratified random sampling method, based on the extent of land ownership < 0,5 hectare, 0,6 to 1 hectare, and > 1 hectare. The results showed that swamp rice farming was profitable with farming income of Rp14.026.652,00 per hectare per cropping season with the R/C of 3,94. Factors that affected the income of swamp rice farming were the life of farmers, land size, and farming experience.